STRATEGI PEMBELAJARAN ESKPOSITORI: Suatu upaya meningkatkan prestasi belajar Bahasa Indonesia pada siswa kelas X-MIA 5 SMA Negeri 24 Bandung - hayati hayati hayati (Universitas Sultan Ageng Tirtayasa, 2020)
This article is the result of research that has focused on improving student learning achievement through the application of expository learning strategies. Because it is improving, the method used is descriptive in the form of classroom action research with 36 respondents in class X-MIA 5 in SMA Negeri 24 Kota Bandung. This research has been able to prove that the application of expository learning strategies can improve student learning achievement in the material concepts of character, content, and values of the hikayat. Collaborating on group methods, simulations, and illustrations through lectures has established the application of this strategy in achieving learning objectives. In addition, classroom management techniques through uniform group guidance and motivation to students provide coloring in the success of this class action research.